Coronavirus Disease 2019 (COVID-19) and Pregnancy: Challenges for Midwifery - Wirifai , Supiya; Luddangam , Pimlada (Journal of Nursing, Siam University, 2022)
In the 21st century, the world has faced one of its huge challenges. A new viral disease called “Coronavirus 2019 (COVID-19)” that has spread widely and has resulted in massive deaths, including among pregnant women. Although, COVID-19 symptoms in pregnancy are similar to infections that occur in the general population, it was found that pregnant women who were infected with the COVID-19 virus resulting in preterm labor, intrauterine growth retardation, fetal distress, premature rupture of membrane, and high rate of cesarean section. Midwives play an important role in caring for pregnant women during the epidemic. Therefore, the midwives should have knowledge, understanding about the Covid-19 diseases and its consequences, clinical assessments, and comprehensive nursing care of diseases. This will enable midwives to plan continuing care in collaboration with a multidisciplinary team. Getting effective care ensures both pregnant women and their babies safe and stay healthy. The article aims to present knowledge about COVID-19 and the challenges of the midwives’ role in caring for pregnant women. This is used as nursing practice guideline to prevent infection and reduce the consequences that may arise when an infection occurs.